KONSTRUKSI IDENTITAS ORANG SASAK DI LOMBOK TIMUR, NUSA TENGGARA BARAT - A. A. Ngr Anom Kumbara (Humaniora, 2008)
This article examines the strategies that Sasak elites employ for the construction of the Sasak self-identity and the reasons why this identity is constructed. Practical anthropology and interpretive-hermeneutic methods were used to investigate these phenomena. The results show that in their attempt to construct the Sasak self identity and to maintain it, the Sasak elites have made use of a wide range of resources at their disposal including religious symbols, local customs and ethnicity.